2020
DOI: 10.1080/15548627.2020.1848130
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mitochondrial quality control mediated by extracellular release

Abstract: Mitochondrial quality control, which is crucial for maintaining cellular homeostasis, has been considered to be achieved exclusively through mitophagy. Here we report an alternative mitochondrial quality control pathway mediated by extracellular mitochondria release. By performing time-lapse confocal imaging on a stable cell line with fluorescent-labeled mitochondria, we observed release of mitochondria from cells into the extracellular space. Correlative light-electron microscopy revealed that majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 44 publications
2
82
0
Order By: Relevance
“…Clearance of depolarized mitochondria under mitochondrial stress has emerged as an alternative mitochondrial quality control pathway. Mitochondria released into extracellular space are predominantly in free form (500 nm-1.5 mm) rather than in membrane-surrounded vesicles (Choong et al, 2020). This finding is consistent with the previous research that free mitochondria and mitoparticles derived from astrocyte spanned a range of sizes from 300 to 1100 nm (Hayakawa et al, 2016).…”
Section: Regulation Of Extracellular Mitochondria Quality Controlsupporting
confidence: 91%
“…Clearance of depolarized mitochondria under mitochondrial stress has emerged as an alternative mitochondrial quality control pathway. Mitochondria released into extracellular space are predominantly in free form (500 nm-1.5 mm) rather than in membrane-surrounded vesicles (Choong et al, 2020). This finding is consistent with the previous research that free mitochondria and mitoparticles derived from astrocyte spanned a range of sizes from 300 to 1100 nm (Hayakawa et al, 2016).…”
Section: Regulation Of Extracellular Mitochondria Quality Controlsupporting
confidence: 91%
“…In addition to mitophagy and MDVs, another recently described neuronal mitochondrial quality control mechanism that may be relevant to peripheral neuropathy is the release of axonal mitochondria into the extracellular space. Such mitochondrial expulsion has been described in the mammalian CNS [352], in C. elegans neurons [353], and has been observed in the context of stresses that damage mitochondria where it appears to complement mitophagy as a quality control mechanism [354]. Furthermore, in retinal ganglion cell axons, and likely throughout the CNS, these released mitochondria can be taken up by astrocytes where they can then be degraded in a process termed transmitophagy [352].…”
Section: Mitochondrial Dynamics and Quality Control In Peripheral Neuropathymentioning
confidence: 92%
“…Recently, Choong et al reported that CH12 cells secrete mitochondria into the culture medium, and the extent of the mitochondrial secretion increased upon treatment of the cells with CCCP or by suppression of PRKN and BNIP3 expression; however, the secretion was decreased by overexpression of PRKN and BNIP3, and it was concluded that the release of mitochondria into the culture medium is a distinct mitochondrial quality control pathway. 64 In this context, resveratrol increased mitochondrial cell‐free DNA in the culture medium of cryopreserved‐warmed embryos and concomitantly, decreased mitochondrial DNA copy number and protein levels in the embryos. 10 , 11 …”
Section: Mitochondrial Dysfunction and Degradationmentioning
confidence: 98%